FORMATION OF POTENTIAL OF QUALITY MANAGEMENT OF DOMESTIC BUSINESS ORGANIZATIONS AS DEVELOPMENT OF MARKETING SYSTEM IN CONDITIONS OF DIGITALIZATION - GARAFONOVA, OLGA; POLISHCHUK, LIYDMYLA; DYKHNYCH, LIUDMYLA; YASHCHENKO, INNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
In the context of globalization processes, the problem of product quality is one of the most important, because high-quality products provide competitive advantages to the manufacturer. The position of domestic products on the market is primarily determined by consumer properties that shape quality. Maintaining high competitiveness is paramount and becomes a crucial factor in the commercial success of any business organization. Therefore, it is important to deeply study the factors that influence the formation of product quality.In the current situation in a market economy, producers are under the constant influence of the competitive environment, which requires them to focus more and more on quality issues. Recently, the management of many business organizations has faced the need for quality management as a means of achieving competitiveness, gaining trust in products from consumers. Therefore, it can be argued that in a market economy, one of the most important internal factors in the development of business organizations is product quality, as it provides an increase in the profits of the business organization based on customer satisfaction. Therefore, building an effective quality management system is an extremely important object of further research into the development of the marketing system in the context of digitalization.The article presents modern approaches to the processes of certification of the quality management system in the context of the formation of quality potential in business organizations. An analytical basis has been formed, which is the basis for the promising development of the food industry and business organizations in the context of digitalization. A feature of the effective activity of business organizations of the food industry of Ukraine is the prospects for the development of the food industry as a whole.
Keywords: quality management; food industry of Ukraine; business organizations; development potential